PENGEMBANGAN MODEL LATIHAN DRIBBLING UNTUK MAHASISWA PENDIDIKAN JASMANI KESEHATAN REKREASI UNIVERSITAS DHARMAS INDONESIA - Maldin Ahmad Burhan (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2020)
This study is a research on the development of exercises which aim to improve the skills of the students of Penjaskesrek UNDHARI. Besides, this research also aims to produce teaching materials for the lecturers of Penjaskesrek UNDHARI. In general, the purpose of this study is to produce a new form of training that is effective in the implementation of soccer . This development research uses the Research and Development development model from Borg and Gall. The location of this research is at UNDHARI soccer field, Dharmasraya Regency, West Sumatra Province. The instruments of this study were questionnaires, questionnaires, and basic football technical test instruments, which used to collect data at the stage: (1) needs analysis (2) ) expert evaluation (3) small group trials); and (4) main trials. Based on the results of trials conducted on 8 basic technique training models of soccer that have been validated by experts, the use of the entire training model in this development can be categorized as valid and suitable as a guide to training basic techniques of soccer for students Healthcare UNDHARI.